Spectrophotometric Analysis of Nitazoxanide in Single and Combined Dosage Form - PANDEY, SHAILENDRA; Shankar Shukla, Ravi; Singh, Vineet; Tiwari, Meena (Asian Journal of Chemistry, 2010)
Two simple sensitive UV spectrophotometric methods for the analysis of nitazoxanide in single and in combined dosage form with ofloxacin were developed and statistically validated. Estimation of nitazoxanide in tablet dosage form was carried out by calibration curve method while graphical absorbance ratio method was used for nitazoxanide and ofloxacin combined tablets. The absorption maxima (lmax) for nitazoxanide and ofloxacin are 268 and 302 nm, respectively. The most striking feature of this method is its simplicity, sensitivity and reproducibility. The method is economical and suitable for routine analysis of nitazoxanide tablets and nitazoxanide and ofloxacin in combined tablet dosage form.